Failure Mode Effect Analysis in Turning of Mild Steel Under MQL Condition - Mazlan, Mohd Rhafiq; Yassin, Abdullah; Abang Kamaruddin, Abang Mohammad Nizam (International Journal of Integrated Engineering, 2023)
FMEA was commonly used to improve production quality by reducing workplace failures and preventing them from happening. Nowadays, tool failures are the most common problems that can be found in the machining practice. Hence, FMEA was used to reduce tool failure occurrence and improve the production quality. In this paper, FMEA analysis was done for a turning process of mild steel. Several turning operations were done, and the failure mode and failure effect were identified. Then, the tool failure effect was studied, and the causes were generated using the Ishikawa diagram. The occurrence, severity, and detection rating were assigned, and the Risk Priority Number (RPN) was generated. FMEA Risk Matrix was used to help provide a visual aid for classifying and categorizing the level of risk. The highest risk was then identified from the highest RPN value, and the cause and prevention methods were generated for each failure effect cause. This study can be used as a guide or reference in the turning process practice for a more effective process.